2017
DOI: 10.26505/djm.13013300328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Horse Riding Simulator with Strengthening Training Program and Conventional Physiotherapy in treatment of Children with Spastic Diplegic Cerebral Palsy

Abstract: Background: Cerebral Palsy is a group of disorders that affect the development and growth of the movement leading to the determination in the activities of the body, especially related to movements. These disorders occur as a result of damage or deterioration in certain parts of the brain. Objective: To evaluate the effectiveness of horse riding simulator with strengthening training program on children with spastic diplegic cerebral palsy and comparing it with conventional physiotherapy program which is used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…The periodical improvements in GMFM scores were evaluated at different levels at baseline, at the end of 4, 8 and 12 weeks in both groups. Regarding the treatment protocol, this study is similar to the study done by Bagheri et al (2017) who conducted study with the same protocol, that is, 15 min of HRS, 3 times per week and addressed the benefits of HRS improving motor functions.…”
Section: Discussionmentioning
confidence: 74%
“…The periodical improvements in GMFM scores were evaluated at different levels at baseline, at the end of 4, 8 and 12 weeks in both groups. Regarding the treatment protocol, this study is similar to the study done by Bagheri et al (2017) who conducted study with the same protocol, that is, 15 min of HRS, 3 times per week and addressed the benefits of HRS improving motor functions.…”
Section: Discussionmentioning
confidence: 74%
“…Twenty-one studies were deleted for not meeting the inclusion criteria (reasons in Figure 1 ). Finally, 12 clinical trials were included in this review [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. All studies provided data for the qualitative synthesis (systematic review), and 10 reported quantitative data for use in the quantitative synthesis (meta-analysis) [ 63 , 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review were conducted between 1998 and 2022 in India [ 64 , 67 ], South Korea [ 65 , 66 , 70 , 71 ], Iraq [ 63 ], Spain [ 69 ], Brazil [ 73 ], Thailand [ 74 ] and the USA [ 72 ]. The included studies reported data from 343 patients with spastic diplegic CP with ages between 2 and 16 years old, of which 56% were male versus 44% female.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations